Nanoformulation of synergistic TLR ligands to enhance vaccination against Entamoeba histolytica. Issue 6 (7th February 2017) - Abhyankar, Mayuresh M.; Noor, Zannatun; Tomai, Mark A.; Elvecrog, James; Fox, Christopher B.; Petri, William A.
Highlights: Nanoliposome adjuvant induced a robust mucosal and systemic response towards an amebiasis antigen. Vaccine induced mucosal IgA inhibited adherence of E. histolytica to target cells in vitro . This adjuvant is compatible with the use of all-trans retinoic acid as a co-adjuvant. The adjuvant showed potential to elicit protective response against E. histolytica . Abstract: Diarrheal infectious diseases represent a major cause of global morbidity and mortality. There is an urgent need for vaccines against diarrheal pathogens, especially parasites. Modern subunit vaccines rely on combining a highly purified antigen with an adjuvant to increase their efficacy. In the present study, we evaluated the ability of a nanoliposome adjuvant system to trigger a strong mucosal immune response to the Entamoeba histolytica Gal/GalNAc lectin LecA antigen. CBA/J mice were immunized with alum, emulsion or liposome based formulations containing synthetic TLR agonists. A liposome formulation containing TLR4 and TLR7/8 agonists was selected based on its ability to generate intestinal IgA, plasma IgG2a/IgG1, IFN-γ and IL-17A. Immunization with a mucosal prime followed by a parenteral boost generated a high mucosal IgA response that inhibited adherence of parasites to mammalian cells. Inclusion of the immune potentiator all-trans retinoic acid in the regimen further improved the mucosal IgA response. Immunization protected from infection with up to 55% efficacy. Our results show that a nanoliposome delivery system containing TLR agonists is a promising prospect for the development of vaccines against enteric pathogens, especially when a multifaceted immune response is desired.